2021
DOI: 10.3390/polym13040545
|View full text |Cite
|
Sign up to set email alerts
|

The Direct 3D Printing of Functional PEEK/Hydroxyapatite Composites via a Fused Filament Fabrication Approach

Abstract: The manufacture of polyetheretherketone/hydroxyapatite (PEEK/HA) composites is seen as a viable approach to help enhance direct bone apposition in orthopaedic implants. A range of methods have been used to produce composites, including Selective Laser Sintering and injection moulding. Such techniques have drawbacks and lack flexibility to manufacture complex, custom-designed implants. 3D printing gets around many of the restraints and provides new opportunities for innovative solutions that are structurally su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 51 publications
2
55
0
Order By: Relevance
“…For the 0HA sample, strong peaks corresponding to various diffraction planes for PEEK have been identified at 18.86°, 20.90°, 22.76°, and 28.75° 2θ, and are attributed to orthorhombic PEEK crystal planes (110), (111), ( 200) and (211), respectively. [11,18] In the composites containing HA (loaded between 5-30% by weight), additional peaks were observed at 25.93°, 31.85°, 32.24, 32.98°, and 34.12° 2θ and correspond to (002), (211), (112), (300), and (202) planes of crystalline HA in accordance with International Centre for Diffraction Data (ICDD) File# 09-0432. Upon increasing the HA concentration in the PEEK/HA composites the intensities of the HA peaks increased (with respect to the PEEK), as would be expected as shown in Figure 3.…”
Section: Xrdsupporting
confidence: 53%
See 3 more Smart Citations
“…For the 0HA sample, strong peaks corresponding to various diffraction planes for PEEK have been identified at 18.86°, 20.90°, 22.76°, and 28.75° 2θ, and are attributed to orthorhombic PEEK crystal planes (110), (111), ( 200) and (211), respectively. [11,18] In the composites containing HA (loaded between 5-30% by weight), additional peaks were observed at 25.93°, 31.85°, 32.24, 32.98°, and 34.12° 2θ and correspond to (002), (211), (112), (300), and (202) planes of crystalline HA in accordance with International Centre for Diffraction Data (ICDD) File# 09-0432. Upon increasing the HA concentration in the PEEK/HA composites the intensities of the HA peaks increased (with respect to the PEEK), as would be expected as shown in Figure 3.…”
Section: Xrdsupporting
confidence: 53%
“…Our previous work studied the crystallinity, morphology, bulk properties, and mechanical properties of the same materials and found that the approach taken here could be used to successfully manufacture PEEK/HA composites up to 30 wt% HA [11]. This worked highlighted that the materials were printable, and importantly could be delivered with mechanical properties that matched those of human cortical bone [11]. Other studies have utilised FFF 3D printing of PEEK/HA composites; however, they only investigated the use of up to 10 wt% PEEK/HA and did not achieve the same mechanical properties as those presented here [5,12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More investigations were based on fused filaments. For example, Krzysztof Rodzeń et al [ 24 ] attempted to directly 3D print functional PEEK/hydroxyapatite composites with fused filaments. C. Yang et al [ 25 ] proposed a temperature-controlled 3D printing method for PEEK, which can realize different degrees of crystallinity and mechanical properties for customized PEEK parts.…”
Section: Introductionmentioning
confidence: 99%